2014
DOI: 10.4028/www.scientific.net/amr.969.85
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of Finite Element and Classical Computing Models of Reinforcement Pavement

Abstract: Within the solution of the vehicle roadway interaction problems the various computing models of the road can be used. The results of the solution show that under certain conditions also simpler computing models can offer applicable results. The submitted paper is dedicated to the comparison of the results obtained from simpler road computing model and from the model based on the finite element method.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 2 publications
0
4
0
Order By: Relevance
“…Computer-aided engineering is not limited to small objects and structures but can be also utilized to solve complex problems of larger structures. Cajka and Krejsa [16] performed numerical analysis of rooflight steel structure and validated their results with experimental tests, whereas complex numerical analyses of bridge structures were presented in [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Computer-aided engineering is not limited to small objects and structures but can be also utilized to solve complex problems of larger structures. Cajka and Krejsa [16] performed numerical analysis of rooflight steel structure and validated their results with experimental tests, whereas complex numerical analyses of bridge structures were presented in [17][18][19].…”
Section: Discussionmentioning
confidence: 99%
“…Results have shown that response mode III is predominant and the response modes I and II are negligible, except of free edges. Based on these results a designer must pay attention at the free edges of delamination front [12][13][14][15]. …”
Section: Resultsmentioning
confidence: 99%
“…A two-subplate sandwich FEM [17]- [21] model which incorporates interface models based on fracture and contact mechanics has been proposed. The interface between sublaminates is modeled by CE.…”
Section: Discussionmentioning
confidence: 99%